Pengaruh Keputusan Investasi, Keputusan Pendanaan, Kebijakan Dividen, dan Kinerja Keuangan Terhadap Nilai Perusahaan ( Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Bandani, Dina Putri, Dr. Fatchan Achayani, S.E., M.Si (2017)
This research aimed to analyze the influence of investment decisions (KI), financing decisions (KP), dividend policy (KD), and financial performance (KK) to corporate value (NP) in a manufacturing companies which listed in Indonesian Stock Exchange (BEI) in the period 2013-2015.The research sample consisted of 17 companies of 154 in a manufacturing companies listed on BEI by the observation numbers of 51 observational data. The sampling method was done by using purposive sampling. The researched data was obtained from IDX. The data analysis technique used in this research is multiple linier regression. Hypothesis testing using t statistics used in this research to test the partial regression coefficients as well as f-statistics to test the significance of the influence together, with the level of significance of 5%. Other than that, all the variables had been tested with the Normality test, Multicollinearity test, Autocorrelation test, and Heteroskidastity test.The result showed that all variables passed the classical assumption test and suitable to be used as research data. T-test statistics on corporate value (NP) predicated that investment decisions (KI), financing decisions (KP), and financial performance (KK) has significant influence on corporate value (NP), whereas dividend policy (KD) has no influence on corporate value (NP).